A revision of the genus Eugorgia Verrill, 1868 (Coelenterata: Octocorallia: Gorgoniidae) - Breedy Shadid, Odalisca (2009)
The species of the gorgoniid genus Eugorgia that occur along the eastern Pacific are taxonomically revised based on original type material of all species described until now, and reference specimens from recent surveys and expeditions. The genus Eugorgia is characterised by having a dominance of double disc sclerites in the coenenchyme which separate this taxon from the other gorgonians with similar external morphology such as Leptogorgia. In this revision, 12 species are recognized as valid and one is synonymised, E. forreri. Lectotypes were assigned for two species in order to establish their taxonomic status, and three varieties were established as species, E. alba, E. excelsa and E. purpurascens. All the species are described and illustrated. Based on the morphology of colonies and sclerites and supported by a phylogenetic analysis, we recognised three species groups within the genus Eugorgia: the “ampla-group” consisting of eight species, with slightly raised polyp-mounds and dichotomous branching or irregular variations of it; the “daniana group”, consisting of three species, with prominent polyp-mounds and pinnate-like branching; and the “rubens-group” consisting of a single species, E. rubens, which is closely related to species within the second group. The fauna herein reported does not represent the diversity or geographical range of the species because more surveys are needed and more material stored in museums needs attention to complete the regional assessment.